An Analysis of the Online Final Examination Items in the Mathematics Course Using the Rasch Measurement Model - Tommy Tanu Wijaya; Jiajie Yan; In In Mutmainah; M. Afrilianto; Tina Rosyana; Xinxin Li (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Abstract. The National Examination in Indonesia has been abolished since 2020. Hence, the Indonesian Junior High School (SMP) makes its final examination items for the 9th-grade, and from the results, the school determines success in the course. The final examination has an important role and significant value in making decisions about students' graduation. Therefore, this study is aimed to analyze the Online Final Examination items in one of the public junior high schools in Bandung. The sample was 234 students in grade 9 using their mathematics examination tests, comprising 20 multiple-choice items with 4 options (A-D), while the data processing used Winsteps software with the Rasch modeling technique. Subsequently, the Rasch model results showed an acceptable people separation statistic of 1.54 and poor person reliability at 0.7<0.8. The item separation statistics was in a good category at 2.21, while the reliability at 0.83 was excellent. Although 4 online final examination items were in the fit category, 16 were good and capable of dividing students according to their abilities. They also provided very detailed data about the quality of the items and the ability of each grade 9 student. Since each test item is included in the fit category, this study contributes information on preparing and analyzing the Online Final Examination to teachers.